Porcine hepatocytes culture on biofunctionalized 3D inverted colloidal crystal scaffolds as an in vitro model for predicting drug hepatotoxicity. Issue 31 (7th June 2019) - Wu, Lingyan; Ferracci, Gaia; Wang, Yan; Fan, Teng Fei; Cho, Nam-Joon; Chow, Pierce K. H.
Abstract : As drug-induced hepatotoxicity represents one of the most common causes of drug failure, three-dimensional in vitro liver platforms represent a fantastic toolbox to predict drug toxicity and reduce in vivo studies and drug attrition rates. Abstract : As drug-induced hepatotoxicity represents one of the most common causes of drug failure, three-dimensional (3D) in vitro liver platforms represent a fantastic toolbox to predict drug toxicity and thus reduce in vivo animal studies and lessen drug attrition rates. The aim of this study is to establish a functional porcine hepatocyte culture using a biofunctionalized 3D inverted colloidal crystal (ICC) hydrogel platform. The performances of non-adhesive bare poly(ethylene glycol)diacrylate (PEGDA) ICCs and PEGDA ICCs coated with either collagen type I or fibronectin have been investigated. Porcine hepatocytes viability, morphology, hepatic-specific functions and patterns of gene expression have been evaluated over a period of two weeks in culture to test diclofenac, a well-known hepatotoxic drug. Interestingly, cells in the fibronectin-functionalized scaffold exhibit different aggregation patterns and maintain better liver-specific function than those in bare ICCs and in collagen functionalized scaffold. We concluded that the 3D cell culture environment and the presence of extracellular matrix (ECM) proteins, especially fibronectin, facilitate hepatocyte viability and maintenance of the liver-specific phenotype in vitro, and enable us to predict hepatotoxicity.